COLLECTIVE ACTIVISM AND VIRAL NARRATIVES: EXPLORING THE SYMBIOSIS BETWEEN SEVEN JEWISH CHILDREN AND THE PALESTINIAN CAUSE VIA ONLINE MEDIA DECONSTRUCTION - Yousif, Marwan Khaleel (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The study explores the intricate relationship between Caryl Churchill's renowned play 'Seven Jewish Children' and the Palestinian cause. It particularly addresses collective activism and the increasing impact of viral narratives that influence public opinion regarding the ongoing Palestinian-Israel conflict and the play. Through the lens of a multidimensional approach, the study employs online media interpretations as a main methodological framework to examine the interaction between collective activism, viral narrative, and the historical significance of the play. The study explores how viral narratives inform and impact public perception toward the play and the serious issues it tackles by utilizing the digital realm, online forums, and social networking platforms, Moreover, it explores how social upheavals and online communities mobilize the collective activism, analyzing the different tactics used to magnify their voices and strive for change. By investigating the play's digital circulation, reactions, and reception, the study reveals the mutually reinforcing relationship between the discursive potency of the play and the Palestinian cause. Furthermore, it explores how viral narratives and online activism may question dominant perceptions, raise awareness, and spark debate about the profound socio-political concerns that are presented in the play. This study contributes to the current scholarship by emphasizing the transformational power of social media platforms and providing insights into the way that collective activism and viral narratives interact to shape public perception and promote support for the Palestinian cause. In the light of the Israeli-Palestinian conflict, it also highlights the value of the play as a historical document that inspires multiple narratives as well as mobilizes unity, opening up new debates about representation, activism, and social transformation.